From Digital Consumers to Knowledge Creators: Reconceptualizing Web 2.0 Integration through a Pedagogical Maturity Continuum in Primary Education - Gürhan, Ethem (Institut Agama Islam Negeri Palangka Raya, 2026)
The rapid digitalization of education has intensified expectations for meaningful technology integration, yet the relationship between Web 2.0 adoption and pedagogical transformation remains theoretically underdeveloped. This study advances a theory-building integrative synthesis to reconceptualize Web 2.0 integration in primary education beyond instrumental use. Drawing on a systematic search of peer-reviewed studies (2019–2024; n = 38), the analysis integrates the Technological Pedagogical Content Knowledge (TPACK) framework, socially mediated self-efficacy, and structural perspectives to explain conditions of transformation. The findings reveal a persistent diffusion–transformation gap, in which technological adoption often enhances instructional efficiency without restructuring epistemological practices. To address this limitation, the study proposes the Pedagogical Maturity Continuum, a developmental framework explaining how teachers progress from technological familiarity to epistemological reconfiguration. The model demonstrates that transformation emerges only through the convergence of TPACK alignment, ecosystem-supported self-efficacy, and institutional coherence. This study contributes a theoretically grounded framework that reframes technology integration as a conditional and developmental process, offering a foundation for future empirical validation and policy design.